Psychiatric and Disabled people: Legal and Human Right aspects - K. Talwar, Upmesh; Duggal, Ashki; Singh, Ravinder (International Journal of Health, 2014)
Legislation forms an important component in the implementation of mental healthcare. Legislation is an expression of society with regard to the way it views and cares for mentally ill individuals. It has long been known that there is a dynamic relationship between the concept of mental illness, the treatment of the mentally ill and the existing Law. Mentally ill persons are vulnerable and required protections and access to treatment programmes, significant degree of choice and respect for autonomy. Though there are several laws but these laws are not able to protect the right of the mentally ill person and person with the disabilities. This paper is emphasized on the human rights and legal provisions for mentally and physically challenged people and reviews the existing rights and their importance for the welfare of these groups and also emphasized on their drawback in an Indian Perspective.